Morfodinâmica de praias e processos erosivos intraurbanos no município de Aracaju/SE - Cruz, Rafael da (2023)
The urban space presents itself as one of the greatest expressions of physical environment transformation. One of them is the development of accelerated erosion with the breaking of the environmental balance by human activities. In all cases, the improper use and handling of urban and/or rural soil lead to the occurrence of accelerated erosion processes, which are often irreversible. Aracaju, following the rule of other expanding urban centers, has been presenting over time problems related to erosion both in the coastal zone and in the intra-urban area, mainly on the slopes located in the north, west, and south regions of the city, which constitute areas of risk potential for the poorest population. In this context, the research, in general terms, aimed to analyze the coastal morphodynamics and intra-urban erosion processes in Aracaju, to contribute to the implementation of public policies that reconcile nature with society, directing local territorial management in the process of soil occupation and use. To fulfill the objectives, during the investigation, the approach used was the General Theory of Systems, associated with the qualitative and quantitative analysis method. The methodological procedures, executed in different stages, were based on a bibliographic survey, as well as cartographic documents and other files; fieldwork, photographic records, and office work with laboratory analyses. Among other results, it was verified that in the coastal zone, the occupation along the coast, disorderly from the beginning, contributed to the intensification of the erosion process, with greater incidences in the mouths of the Sergipe rivers (Praia dos Artistas - Coroa do Meio) and Vaza Barris (Praia do Viral - Mosqueiro), where the destruction caused by the movement of waves and dynamics of the tides characterizes the action of the negative sediment budget. In the municipal intra-urban space, the erosive action gains expressiveness on the slopes that exhibit features in different stages of evolution (furrows, ravines, and gullies), which indicates possible risks for the population that occupies them and their surroundings. Thus, it can be concluded that the coastline of the municipality in different time scales has been experiencing advances and retreats of the coastline, demonstrating a tendency to progradation, stability, and erosion in very diversified degrees of exposure and physical vulnerability, being perceptible the manifestation of the phenomenon severe erosive to a moderate degree at the river mouths and at some specific points, generating deficits in the sediment budget. In the intra-urban space, potentially favorable locations for the development of furrows, ravines and gullies should include, in the preparation of the Geotechnical Map, studies of susceptibility to erosion, allowing guidelines not only of a preventive nature against the beginner of gullies, but also as a fundamental condition for the correct conception and success of correction building works, when the erosion process is already installed.